Memories through images and stories: teaching art educational experiences (Palíndromo, 2023)
This paper shows an examination of the experience performed with Visual Arts students at Universidade do Extremo Sul Catarinense (Unesc) between 2013 and 2016, in “Engraving and Research” and “Screen Printing and Research” courses. The study purpose was to identify which subject students bring with their memories about their experiences at school relating to Arts course in basic education, as stories and images, intending to understand where the role of Arts course is, and which has been the role of engraving art regarding artistic languages, intending to understand qualification process for Arts education teaching profession. The study methodology was developed as a qualitative and artographic approach, based on visual productions and students’ memories/narratives. Data were collected through applicating a questionnaire. According to data analysis, we noticed that engraving is rarely mentioned as an artistic language developed at school, as it is emphasized drawing and painting. Thus, one may conclude that artistic languages, including printmaking poetics, need to be further developed in classrooms, and Art education needs to be appreciated with adequate spaces, as a source of sensitivity, empathy, and basic education qualification.
Keywords: Memory; Experience; Engraving; Art Education; Teacher Qualification